The provision on Web accessibility and VOD access services for people with disabilities: A case study of South Korea - Heakeng Vivian Choi (International Telecommunications Society (ITS), 2018)
As more people around the world are watching video contents through online, the subject of web accessibility and VOD accessibility is currently being debated at the worldwide policy level. Currently, most linear television content providers are required to provide a certain proportion of their content accessible through a subtitle, audio description, or signing services. However, in Korea, there is no policy or regulation for accessible broadcasted VOD contents. Therefore, this paper conducted an in-depth interview with media professionals, policy advisors, community media foundation's viewers support department, video content service providers, and accessibility advocates to discover current issues of a provision on VOD accessibility for the people with disability and find out impediment factors that cause delays in providing accessible services under fast-changing ICT environment. Referencing the case of existing legislation of U.S., U.K and W3C recommendations, this paper suggests what to do in future access service provision.
Keywords: 330; Disability; Web Accessibility; VOD accessibility; Accessible service; Policy; ICT